Ethnic Marketing: A Strategy for Marketing Programs to Diverse Audiences - Lisa A. Guion; Heather Kent; David C. Diehl (EDIS)
Revised! This document is FCS9223, one of a series by Lisa A. Guion and David C. Diehl that includes articles on planning programs to effectively reach diverse audiences. Published by the Family, Youth and Community Sciences Department, June 2010.